From work one’s ass off to bite one’s face off: Understanding the degree of idiomaticity through syntactic and semantic inheritance in a network of (originally) resultative constructions - Sánchez Fajardo, José A. (Complutense Journal of English Studies, 2024)
This study is aimed at exploring the degree of idiomaticity of resultatives characterized by the structure [[V]i[pd]j[N]koff] through a qualitative examination of [V], [N], and the property of telicity. Based on a random extraction of 1,000 concordances from the English Corpus enTenTen21, findings show that the network of constructions is made up of three Types (‘Intensification’, ‘Astoundment’, and ‘Detachment’) and ten Subtypes, with ‘body part’ being the most frequent [N]. Also, the (sub)schemas in the network originate from the inheritance of at least one of the following properties: verbal intensification, (a part of) someone as recipient of an action, and detachment of such a part.
Keywords: idiomaticity; compositionality; construction grammar; network of constructions; telicity; resultativeness